Pengembangan Media Pembelajaran E-Komik Berbasis Model ADDIE pada Materi Identitas Masyarakat untuk Meningkatkan Motivasi Belajar Siswa Kelas IV Sekolah Dasar - Kadek Rika Damayanti; I Gede Suwindia; Gusti Ngurah Arya Yuda Parmita (Prodi Pendidikan Guru Sekolah Dasar, 2026)
This research was motivated by the low use of interactive digital learning media in elementary schools, specifically in Pancasila Education, which implicates low student learning motivation. This study aims to describe the design and test the validity and practicality of E-Comic learning media on community identity material for 4th-grade elementary school students. This is a Research and Development (R&D) study using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The research subjects included one subject matter expert, one media expert, one language expert, and practitioners (teachers and students). Data were collected using observation, interviews, and questionnaires, which were then analyzed using descriptive quantitative and qualitative methods. The results showed that: (1) The design of E-Comics involved using Canva and Flip PDF Plus Corporate to create interactive visual narrative media; (2) E-Comic media was declared highly valid by experts with a Gregory index above 0.80; (3) The practicality test results by teachers reached 79% and students reached 77%, falling into the practical category. Thus, this E- Comic media is feasible for use as a learning tool to enhance student engagement and motivation in understanding community identity material.